(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main aim of the study is to know the risk management initiatives taken by commercial banks and compare risk management policies of nationalised and private banks. The secondary data relevant to the study have been gathered from published sources like the RBI publications such as reports on trends and progress of banking in India, statistical tasks relating to banking in India, RBI Annual Report, RBI Bulletins and Report on Currency and Finance, besides Books, Annual Reports of Commercial Banks, Reports of various Committees appointed by RBI and articles published in various Standard textbooks, Journals and Magazines. The papers presented by experts in various conferences have also been reviewed for the purpose of analysis and suggestions. It is found that almost all the banks have put in place adequate risk management architecture in response to BASEL II guidelines. In compliance with RBI guidelines for appropriate risk management structure, most of the banks have taken several initiatives to manage the risks. It has been observed that most of the banks have put in place Internal Capital Adequacy Assessment Process (ICAAP) to deal with exceptional risks peculiar to bank while others are developing their capabilities to improve risk management process. So, overall commercial banks in India have developed requisite risk management framework to tackle the risk issues with a view to adopt Basel II in line with RBI guidelines